Overcoming cultural barriers in open innovation processes through intermediaries: a theoretical framework. Issue 3 (1st August 2017) - Aquilani, Barbara; Abbate, Tindara; Codini, Anna
Abstract: Certain cultural barriers, such as insufficient openness, aversion to risk-taking, organizational inertia and specific syndromes could inhibit successful Open Innovation processes. However, how Open Innovation Intermediaries help in overcoming obstacles to successfully achieve Open Innovation processes, has not yet been analysed in depth. This paper aims to fill this gap, relying on extant contributions of Open Innovation processes, Open Innovation Intermediary features and types. Based on the distinction between outside-in, inside-out and coupled Open Innovation processes, the theoretical framework developed here identifies specific cultural barriers affecting each process and suggests which intermediary types could be more suited to sustain firms undergoing these processes. The framework supports firms opening up their internal R&D activities to choose the intermediary type most suitable for adaption to an appropriate culture, as well as overcoming any possible cultural barriers.